The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0034-71672003000500009
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento das ações de enfermagem do CIPESC às intervenções de enfermagem da NIC

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
3
0
8
Order By: Relevance
“…In compliance with the NIC (9) , these activities were identified in the Health System (52%), Safety (16%), Physiological: Complex (10%), Community (10%) and Family (10%) (21) domains. The relevant percentage observed in the Health System domain corroborates the findings of this present research and other studies in the health care area (11)(12)(13) .…”
Section: D Gaidzinski Rr Santos Fm Gonçalves Cs Fugulin Fmtmentioning
confidence: 99%
“…In compliance with the NIC (9) , these activities were identified in the Health System (52%), Safety (16%), Physiological: Complex (10%), Community (10%) and Family (10%) (21) domains. The relevant percentage observed in the Health System domain corroborates the findings of this present research and other studies in the health care area (11)(12)(13) .…”
Section: D Gaidzinski Rr Santos Fm Gonçalves Cs Fugulin Fmtmentioning
confidence: 99%
“…Cross mapping is a process of comparing data by using words with identical or similar meanings (8) . Studies have shown the validity of the methodology in comparing non-standardized nursing languages to uniform nursing classification terminologies identifying similarities between the terms (6)(7)(8)(9)22) .…”
Section: Discussionmentioning
confidence: 99%
“…It should, however, be noted that some Brazilian nurses recognize, utilize and have demonstrated the advantages of the registration of the steps of the NP and of the use of standardized nursing languages in the clinical practice (4)(5) . Others have shown its use in nursing research (identification, mapping and validation studies) (6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…A escala Stratify foi encontrada em 13 estudos (ANG et al, 2007;BARKER et al, 2011;SMITT;FORSTER;YOUNG, 2006;HAINES et al, 2007;KO et al, 2012;MILISEN et al, 2007;OLIVER et al, 2004;OLIVER, 2008a;PAPAIOANNOU et al, 2004;SCOTT et al, 2007;VASSALLO et al, 2005;VASSALLO et al, 2008;WEBSTER et al, 2010), a de quedas de Morse, em nove (ANG et al, 2007;CHAPMAN;BACHAND;HYRKA, 2011;CHOW et al, 2007;HAINES et al, 2007;McFARLANE-KOLB, 2004;O"CONNELL;MYERS, 2002;OLIVER et al, 2004;SCOTT et al, 2007;G EEST;MILISEN, 2006a) LOVALLO et al, 2010).…”
Section: Quedasunclassified